Peningkatan Kepercayaan Diri Peserta Didik melalui Pembelajaran Berbasis Proyek (Project-Based Learning) di SDN 31 Mataram - Watoni, Khaerul; Tahir, Muhammad; Suciani, Baiq Ria (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to enhance students’ self-confidence through the implementation of the Project-Based Learning (PBL) model at SDN 31 Mataram. The research employed a Classroom Action Research (CAR) method conducted in three cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects were third-grade students who initially exhibited low levels of self-confidence. The results indicate that the implementation of PBL effectively improved students’ self-confidence, as reflected in their increased willingness to express opinions, ability to face challenges, and active participation in group discussions. In addition, students’ academic performance showed a significant improvement, with the average score increasing from 69.13 to 90.40. PBL also contributed to the development of students’ social skills, such as collaboration and communication. These findings confirm that PBL is an effective learning method for fostering an inclusive learning environment, supporting character development, and improving the overall quality of education.